Consequences and Adaptations in Medical Education during the COVID-19 Pandemic: Medical Students’ Perspective in a Malaysian Public Institution - Ahmad Anwaar Muhammad Saifullah; Nour Hanan Daniah Mohd Bakhit; Maimunah Binti Abdul Muna'aim; Suhaila Sanip; Mohd Rahman Omar (USIM Press, 2024)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become one of the most disastrous health crises of the present world. The COVID-19 pandemic imposes unprecedented challenges for medical education globally. We describe how the pandemic has disrupted the medical education landscape from the students' perspectives and how medical students from a public higher institution adapted to the changes made to comply with the various government agencies' guidelines to contain the spread of COVID-19 while fulfilling the course requirements. The utilisation of numerous innovative online applications enabled the students to participate in numerous teaching and learning activities (TLA) with more flexible scheduling of the classes, participated in a series of online case-based discussions, clinical practice guideline (CPG) discussions, case presentations and objective structured clinical examination (OSCE) simulations. Students also joined TLAs conducted by other institutions both locally and abroad. In addition, students had collaborated among themselves and students from other institutions to conduct online peer-teaching activities. Perhaps, the main challenges for online classes were being unable to perform medical procedures and technical issues, commonly the poor internet connectivity. In regard to physical examinations, students performed it on members of their household instead of real patients. Learning medicine from a distance also gave us an opportunity to taste telemedicine which may be the future of medical practice. Students and academics should be adaptive, resourceful and resilient in facing these changes together. The institution needs to look at all stakeholders' perspectives to respond to the changes in the medical education landscape.